Pembingkaian Perjuangan Tanah Orang Mentawai Dalam Konflik Kehutanan - Nurhayati Nurhayati; Afrizal Afrizal; Jendrius Jendrius (Jurnal Ilmu Sosial dan Ilmu Politik)
The geographical location and growth patterns have never been touched by human intervention, making the Mentawai forest have a unique composition. Implementation of economic growth in land control through market mechanisms and state intervention. State intervention in the land and forestry sectors changes the land use map on Siberut Island. Limiting residents' rights in managing, utilizing natural resources, and ownership. This study focuses on the Siberut forestry conflict in Saliguma Village, Siberut Tengah District, Mentawai Islands Regency. The Provincial Government reserves ± 20,030 hectares of land for PT-Biomass Andalan Energi for Calliandra (Calliandra Calotthyrsus), gamal (Gliricidia Sepium), and lamtoro (Leucaena leucocephala) Industrial Plants. The purpose of the study was to describe the framing and basis for framing of the Saliguma Village people in the conflict with PT. BAE. Using the Symbolic Interactionism theory developed by Herbert Blummer with a qualitative research approach. Researchers collected and analyzed data in the form of words, human actions, interviewed Traditional Leaders, Village Heads, Sikebukkat Uma, land cultivators, and sympathizers of the Saliguma Village people. The results of the study rejected the investment plan to develop Industrial Plantation Forests in Saliguma Village. The Saliguma Village people framed the land as ancestral land, sacred land, land as a source of livelihood, customary land, their village is prone to flooding, and they were deceived by the company. The basis for the framing of the Saliguma Village people is the ancestral rights to the land and the sustainability of the lives of the Saliguma Village people.